The validation of the Supervision of Thesis Questionnaire (STQ). (June 2018) - Henricson, Maria; Fridlund, Bengt; Mårtensson, Jan; Hedberg, Berith
Abstract: Background: The supervision process is characterized by differences between the supervisors' and the students' expectations before the start of writing a bachelor thesis as well as after its completion. A review of the literature did not reveal any scientifically tested questionnaire for evaluating nursing students' expectations of the supervision process when writing a bachelor thesis. Objectives: The aim of the study was to determine the construct validity and internal consistency reliability of a questionnaire for measuring nursing students' expectations of the bachelor thesis supervision process. Design & Methods: The study had a developmental and methodological design carried out in four steps including construct validity and internal consistency reliability statistical procedures: construction of the items, assessment of face validity, data collection and data analysis. Settings & Participants: This study was conducted at a university in southern Sweden, where students on the "Nursing student thesis, 15 ECTS" course were consecutively selected for participation. Of the 512 questionnaires distributed, 327 were returned, a response rate of 64%. Results: Five factors with a total variance of 74% and good communalities, ≥0.64, were extracted from the 10-item STQ. The internal consistency of the 10 items was 0.68. The five factors were labelled: The nature of the supervision process, The supervisor's role as a coach, The students' progression to self-support, The interaction between students and supervisor and supervisor competence. Conclusions: A didactic, useful and secure questionnaire measuring nursing students' expectations of the bachelor thesis supervision process based on three main forms of supervision was created. Highlights: Supervisors can use STQ to facilitate changes to the pedagogical setup of supervision or lectures. STQ can be used to mind the gap of expectations of the supervision process between students and supervisors. The students' expectations of the three main forms of supervision can be measured. The higher education authority can employ the STQ to enhance the quality of supervision in writing thesis. A didactic questionnaire for measuring nursing students' expectations of the supervision process have been developed.